Rogue - Steel, Danielle (New York : Random House Large Print, 2008)
Blake, a millionaire dot-com entrepreneur and Maxine a psychiatrist specializing in childhood trama and adolescent suicide are divorced. Maxine is about to marry Dr. Charles West when a devastating earthquake strikes near one of Blake's palatial foreign homes and he sees hundreds of orphaned children in need of shelter. Now Blake wants Maxine in his life again, as a partner in a humanitarian project that could change countless lives.
Keywords: Divorced parents -- Fiction; Life change events -- Fiction; Large type books; Love stories; Love stories